Development of a high throughput drug screening assay to identify compounds that protect oligodendrocyte viability and differentiation under inflammatory conditions. (December 2016) - Lariosa-Willingham, Karen; Rosler, Elen; Tung, Jay; Dugas, Jason; Collins, Tassie; Leonoudakis, Dmitri
Abstract Background Newly proliferated oligodendrocyte precursor cells (OPCs) migrate and surround lesions of patients with multiple sclerosis (MS) and other demyelinating diseases, but fail to differentiate into oligodendrocytes (OLs) and remyelinate remaining viable axons. The abundance of secreted inflammatory factors within and surrounding these lesions likely plays a major inhibitory role, promoting cell death and preventing OL differentiation and axon remyelination. To identify clinical candidate compounds that may protect existing and differentiating OLs in patients, we have developed a high throughput screening (HTS) assay that utilizes purified rat OPCs. Results Using a fluorescent indicator of cell viability coupled with image quantification, we developed an assay to allow the identification of compounds that promote OL viability and differentiation in the presence of the synergistic inflammatory cytokines, tumor necrosis factor α and interferon-γ. We have utilized this assay to screen the NIH clinical collection library and identify compounds that protect OLs and promote OL differentiation in the presence of these inflammatory cytokines. Conclusion This primary OL-based cytokine protection assay is adaptable for HTS and may be easily modified for profiling of compounds in the presence of other potentially inhibitory molecules found in MS lesions. This assay should be of use to those interested in identifying drugs for the treatment of MS and other demyelinating diseases.